2018
DOI: 10.1016/j.micpath.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 peptide is able to induce an anti-parasitic effect in human placental explants infected by Toxoplasma gondii

Abstract: This study was conducted to investigate annexin A1 (ANXA1) functions in human placental explants infected with Toxoplasma gondii (T. gondii). We examined the first and third trimester placental explants infected with T. gondii (n = 7 placentas/group) to identify the number and location of parasites, ANXA1 protein, potential involvement of formyl peptide receptors (FPR1 and FPR2), and COX-2 expressions by immunohistochemistry. Treatments with Ac mimetic peptide of ANXA1 were performed to verify the parasitism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We observed that both inhibitors did not alter the viability of human villous explants and were also able to strongly reduce the T. gondii intracellular proliferation. Studies demonstrate that the annexin A1 peptide was able to reduce parasitism in villous explants infected by T. gondii , and this was related to a decrease in COX-2/PGE 2 production 84 . Regarding to cytokines production, we observed that only infected villous decreased the MIF production and increased IL-10, suggesting a possible escape mechanism for T. gondii , besides inducing a high production of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that both inhibitors did not alter the viability of human villous explants and were also able to strongly reduce the T. gondii intracellular proliferation. Studies demonstrate that the annexin A1 peptide was able to reduce parasitism in villous explants infected by T. gondii , and this was related to a decrease in COX-2/PGE 2 production 84 . Regarding to cytokines production, we observed that only infected villous decreased the MIF production and increased IL-10, suggesting a possible escape mechanism for T. gondii , besides inducing a high production of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our previous study showed that human trophoblast cells treated with PGE 2 presented higher susceptibility to T. gondii infection (RH strain), evidencing that PGE 2 can facilitate parasite proliferation (Barbosa et al, 2014). Additionally, it was demonstrated that annexin A1 decreased parasitism rate in human placenta infected by T. gondii and it was associated with reduced levels of PGE 2 and COX-2 (Oliveira-Cardoso et al, 2018). Thus, to control the parasite replication, the host cells should reduce COX-2 expression to dampen the T. gondii susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal GC metabolism is also responsible for spontaneous miscarriages [ 19 ]. GC activity is mediated by the calcium-dependent phospholipid binding protein, Annexin A1 (ANXA1) [ 20 ]. Nevertheless, the potential applications for lipoxin A4 in the area of reproductive biology remain unexplored and require further research (Fig.…”
Section: Introductionmentioning
confidence: 99%